Partnerships to increase open weather data's impact - Kamau, Kiringai (Technical Centre for Agricultural and Rural Cooperation, 2018)
Climate warming affects the water cycle, which impacts negatively on agricultural production and derails the cyclical effects associated with weather predictions and agricultural seasonality. Making use of weather data could help farmers to mitigate to the circumstances and increase farm productivity. To succeed, pragmatic public-private multi-stakeholder partnerships are required.